Family socioeconomic code of childhood overweight and obesity in North Macedonia - Stamenova, Aleksandra; Mihajlova, Katerina; Wallace S. Lorraine; Spiroski, Igor (Karger Publishers, 2023)
Background/Aims: Globally, childhood overweight and obesity rates have steadily increased over the past few decades. Drawing from a nationally representative sample of children in North Macedonia (MKD), the aims of our study were to: (1) estimate rates of childhood overweight and obesity and (2) explore associations between family socioeconomic status (SES) indicators and overweight and obesity rates. Methods: As part of the 5th round of the World Health Organization (WHO) European Childhood Obesity Surveillance Initiative (COSI), a cross-sectional study was conducted with MKD children (aged 6-9 years) and their parents/caregivers. Each child’s anthropometric measurements (height, weight) were objectively assessed, family indicators of socioeconomic status (SES) and demographic characteristics were collected through parental/ caregiver completion of a questionnaire. Mirroring methodology employed in previous WHO COSI studies, SES was assessed by self-reported level of parental education attainment (low, medium, and high), parental employment (low and high), and family-perceived wealth (low, medium, and high). Children with missing data on anthropometric measurements and/or SES variables were excluded from our analyses. Childhood overweight and obesity were defined using established WHO 2007 cut-offs. Differences across SES categories were tested using Pearson χ2 test. Statistical significance was set at 0.05 a priori. Results: A total of 2498 children were included in the sample (boys: n=1215 and girls: n=1283). Overall prevalence of overweight was 19.3% while obesity was 20.0%. Level of urbanization of the family’s place of residence (p=.002), language spoken at home (p=.002) and parental employment (p<.001) were significant predictors of childhood overweight or obesity. MKD children at greatest risk of overweight or obesity lived in an urban area, spoke Macedonian at home, and had parents with higher levels of employment. Conclusions: To our knowledge, our study is the first to explore overweight and obesity rates in relation to the family environment, among a nationally representative sample of children and their families. Overall, a large proportion of young children are overweight and affected by obesity. Additionally, our findings indicate that the family environment is relevant determinant of childhood obesity and warrants further investigation to develop evidence-based public health interventions in the future.